Homework in the learning process (2000)
A problem has been observed that creates difficulties in the normal and productive development of the English courses. Without any doubt, doing homework is very important in the learning process of a new language. Doubtless it affects the student’s active participation in the classroom and his relationship to partners and teachers. Because of this, a research project was done with the aim to finding out strategies to ensure students do homework and make it part of the learning process, erasing the image of homework as a punishment.